1995
DOI: 10.1002/1098-108x(199504)17:3<305::aid-eat2260170312>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Early trauma, dissociation, and late onset in the eating disorders

Abstract: Although the majority of patients with anorexia nervosa and bulimia nervosa develop these disorders in their teens and 20s, some patients develop an eating disorder in their 30s, 40s, or 50s. We present a subgroup of patients with the following pattern of symptoms and historical detail: (1) severe sexual and physical abuse by family members; (2) relatively good premorbid professional and marital adjustment (considering later difficulties) though characterized by (3) hypomania, binge eating, and morbid obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 2 publications
4
16
1
Order By: Relevance
“…This result concurs with earlier findings that a subgroup of patients with eating disorders experienced substantial psychological dissociation [35,38]. About one-third surpassed the SDQ-5 cut-off in the screening for dissociative disorders.…”
Section: Discussionsupporting
confidence: 92%
“…This result concurs with earlier findings that a subgroup of patients with eating disorders experienced substantial psychological dissociation [35,38]. About one-third surpassed the SDQ-5 cut-off in the screening for dissociative disorders.…”
Section: Discussionsupporting
confidence: 92%
“…69 Furthermore, individuals with BED were also found to display more difficulties regarding externally oriented thinking, 67 while other studies did not support this finding. 80 Comparisons to individuals with BN yielded fewer difficulties regarding interoceptive awareness in individuals with BED, 73,76,81,82 while other studies reported no dif-ferences, 80,83,84 especially after controlling for age and depression. Interoceptive awareness was assessed in 16 studies using the Interoceptive Awareness subscale of the Eating Disorder Inventory or the Eating Disorder Inventory-2.…”
Section: Self-report Measuresmentioning
confidence: 86%
“…Rates of onset are low over the age of 25 years (Hay, 2004;Hoek, 2006;Hudson et al, 2007, Patrick & Stahl, 2009 and rarely reported over the age of 40 years. The few studies available include 2 patients with onset after 40 years (Mynors-Wallis, Treasure, & Chee, 1992), a single case study with onset at 41 years (Gupta, 1990), 2 patients with onset in the 40s (Tobin, Molteni, & Elin, 1995), and 11 patients with onset over the age of 40 years (Beck, Casper, & Andersen, 1996). Cumella and Kally (2008) reported 50 cases with onset at 40 years or older.…”
Section: Research-article2013mentioning
confidence: 99%